(untitled) (Mustansiria Dental Journal, 2022)
The aim of study: this study was done to assess the clinicopathological features including gender, age, and clinical variations of Twenty Two diagnosed oral pyogenic granuloma in Iraqi patients attended Al Hussein Teaching Medical Center, Karbala city Materials and Methods: A retrospective study for the twenty two cases (22) diagnosed as Pyogenic Granuloma was achieved, the submitted biopsies during a3 years period from January 2018 to March 2021 at Al Hussein Teaching Medical Center, Karbala Health Office, Iraqi Ministry of Health. Data for the following parameters were reported gender, age, site, and clinical presentation (size, base attachment, surface and color).